Pengembangan Model Manajemen Pelatihan Pendidikan Karakter Berdasarkan Door (Diversity, Optimism, Option For the Poor, Respect) Untuk Peningkatan Kinerja Guru di Yayasan Betlehem Bandar Baru - Yohanes Kefi; Syawal Gultom; Saut Purba (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
The orientation of educational institutions is busy with exam scores, and academic grades are the main prerequisites for graduation. As a result, the product produced by students is how high the report card score is and discredits the values of character, life and morality. This causes students to lose focus on character education. For this reason, teachers as the main milestone in learning in the classroom are required to create a learning atmosphere with character based on DOOR (Diversity, Optimism, Option for The Poor, Respect). This is because the character based on DOOR is a guideline in the ministry at the Bethlehem Bandar Baru Foundation. The objectives of the study are: (1) To describe the management model of character education training based on DOOR; (2) Determine the feasibility of the character education training management model based on DOOR; and (3) Determine the effectiveness of the implementation of character education training management based on DOOR at the Bethlehem Bandar Baru Foundation. The research uses a research and development approach to develop a model to improve teacher performance at the Betlehem Bandar Baru Foundation. The research sample is 59 teachers at the Bethlehem Bandar Baru Foundation. The results of the study show: (1) The training model developed is feasible to be used in an effort to improve the performance of teachers of the Bethlehem Bandar Baru Foundation, through the following stages: planning, organizing, moving, and supervising; (2) The training model is effectively used to improve the performance of teachers of the Betlehem Bandar Baru Foundation. There was an increase in teacher performance in the following aspects: learning planning by 42.05%; the implementation of learning is 29.74%; and assessed learning outcomes by 59.49%; and (3) a character training model developed practically for improving teacher performance at the Bethlehem Bandar Baru Foundation, obtained N-Gain Score g = 0.76 > 0.7 (small group trial) and g = 0.79 > 0.7 (limited wide trial); The resulting products were 76.40% (small group trials) and 79.08% (limited wide trials) with the effective category. Based on the results of the study, it is suggested that the improvement of teacher performance at the Bethlehem Bandar Baru Foundation must be carried out with integrated planning, organization, implementation and supervision between the Archdiocesan Foundation, the Foundation's internal supervisors, principals, and teachers.